Promoting Gender-Just Family Relations through Fiqh Mubadalah in Migrant Worker Communities - Sri Wahyuni, Leny (GUYUB: Journal of Community Engagement, 2025)
Referring to BP2MI data, in 2023 Indramayu was the largest contributor of Indonesian migrant workers (PMI), accounting for 6.97% of the national total. Beyond its economic benefits, labor migration generates persistent challenges in family relations, including role imbalances, double burdens, and weakened spousal communication. This program introduces Fiqh Mubadalah as an innovative framework for social transformation in migrant worker families. Using a Participatory Action Research (PAR) approach, the program involved 30 participants from prospective and retired PMI families in Krangkeng District, Indramayu. It aimed to enhance awareness of mufa’alah (collaboration) and musyarakah (mutual participation) within families, strengthen healthy and non-dominative communication, promote equitable division of household roles and responsibilities, and encourage mindset and behavioral changes aligned with mubadalah principles. The intervention was implemented through three stages: socialization, training, and monitoring. Its effectiveness was assessed using pre- and post-activity questionnaires, structured observations, and participant self-reflections based on clear indicators. The results show that 86.67% of participants increased their understanding of gender-just family relations grounded in mufa’alah and musyarakah. Furthermore, 70% adopted healthier communication patterns, 80% applied a fairer distribution of household roles, and 90% demonstrated sustained commitment to practicing mubadalah principles in daily family life. These findings indicate that the mubadalah-based PAR model effectively addresses gender inequality, strengthens family resilience, and produces relational outcomes oriented toward maslahah. As an operationalized model of Fiqh Mubadalah, this program offers a transferable framework for promoting socially just and inclusive family relations in other migrant worker contexts.